Desenvolvimento e caracterização de linguiça frescal de Tambaqui (Colossoma macropomum) - Sleder, Fernando (2015)
In general, fish is still sold in its entirety (whole body) cooled or frozen, with no previous processes included to add value and convenience. Processed products have different sensory attributes, in addition to ease of preparation. The objective of this study was to develop and characterize, through physicochemical, microbiological and sensory traits, a sausage based on tambaqui fish (Colossoma macropomum). Three formulations, different as to the percentage of fat — 0, 4.5, and 9% — were developed. To determine shelf life, samples of the products were stored refrigerated at 4 ºC for 12 days and microbiological analyses were performed on days 0, 3, 7, and 12. Analyses of centesimal composition, shear force, cooking weight loss and water-holding capacity were carried out. The expiration date of the sausages was estimated as seven days of storage. The treatments showed high acceptance rates, above 70%; however, the treatment with 9% fat showed the highest mean values in the evaluated attributes. The centesimal composition of the treatments showed the following variations in g/100 g: moisture, 72.73 to 68.82; protein, 18.85 to 18.90; lipids, 2.90 to 8.33; and ash, 3.86 to 4.20. Shear force varied from 5.92 to 8.14 N; water-holding capacity varied from 71.83 to 74.71%; and cooking weight loss, from 24.21 to 26.59%.